TEACHER AS RESEARCHER: EXPLORING COMPETENCIES AND CHALLENGES OF URBAN AND RURAL ENGLISH SCHOOL TEACHERS IN ACEH - Husna, Faizatul; Sari, Desi Ratna (Journal of English Language and Education, 2024)
Professional teachers are required to possess both pedagogical skills and good writing abilities, which are essential for their professional development. However, many teachers in Aceh, Indonesia encounter challenges in writing scientific papers. This study explores and compares their perceived abilities in conducting classroom action research, as well as the challenges faced by English teachers in urban and rural areas. A mixed-methods research design was employed, conducted in schools across Great Aceh, West Aceh, and South Aceh provinces. The sample comprised 16 teachers, who participated through questionnaires and interviews. The findings reveal significant differences in research abilities between urban and rural teachers. Urban teachers demonstrate greater readiness for conducting classroom action research compared to teachers in rural areas. Factors underlying these challenges include limited time due to heavy teaching loads, the need for peer support in research activities, inadequate school facilities, and insufficient training